The interplay of biopsychosocial factors and quality of life in inflammatory bowel diseases: a network analysis - Thomann, Anne K.; Knödler, Laura-Louise; Karthikeyan, Sandeep; Atanasova, Konstantina; Bernstein, Charles N.; Ebert, Matthias; Lis, Stefanie; Reindl, Wolfgang (Journal of clinical gastroenterology, 2023)
Goal: The aim of this study was to investigate the network of biopsychosocial factors and quality of life (QoL) in persons with inflammatory bowel diseases (IBDs) and explore the influence of psychological factors on the course of the disease. -Background: -QoL of persons with IBD depends on disease activity but also on numerous interacting psychosocial factors. The influence of psychosocial factors on the disease course in controversially discussed. - Materials and Methods: - In 2 independent IBD samples (sample 1: n=209, anonymous internet survey; sample 2: n=84, outpatients with active disease), we measured QoL, anxiety, depression, illness identity, self-esteem, loneliness, childhood trauma, and visceral sensitivity with questionnaires. In addition, fatigue, hemoglobin levels, and response to therapy were assessed in sample 2. We estimated multiple regularized partial correlation networks and conducted accuracy and stability tests of the networks. - Results: - In both samples, QoL had the strongest relationships with visceral sensitivity and the illness identity engulfment. Depression was the most central factor in the networks. Baseline depression scores, visceral sensitivity, and engulfment were associated with response to therapy in sample 2. - Conclusions: - This first network study to assess the interplay between biopsychosocial factors and QoL in IBD reveals a comparable network structure in 2 samples. Results partly replicate findings from previous studies with regard to the importance of depression and yield information on the central role of the newly introduced concepts of illness identity and visceral sensitivity. Preliminary findings point to an influence of these parameters on the disease course, which indicates their role as a possible target in individualized therapy.